Dermoscopic findings of congenital melanocytic nevi. Hair component and multifocal hypopigmentation. - Ciampo, L.; Mazzotta, F.; Scanni, G.; Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2004)
The dermoscopic findings of 78 congenital melanocytic nevi are examined. Multifocal hypopigmented areas are characteristic of these nevi and contribute to their polymorphism. These regularly distributed areas are shown in 31/78 nevi and often -18/31 nevi- are centered by hypertrophic hairs. This finding is more evident than in normal skin, probably due to the presence of hypertrophic hairs and to the contrasting peripheral pigmentation.